Hydration level dependence of the microscopic dynamics of water adsorbed in ultramicroporous carbon. (January 2017) - Mamontov, E.; Yue, Y.; Bahadur, J.; Guo, J.; Contescu, C.I.; Gallego, N.C.; Melnichenko, Y.B.
Abstract: Even when not functionalized intentionally, most carbon materials are not hydrophobic and readily adsorb water molecules from atmospheric water vapor. We have equilibrated an ultramicroporous carbon at several levels of relative humidity, thereby attaining various hydration levels. The water molecules were adsorbed on the pore walls (but did not fill completely the pore volume) and thus could be better described as hydration, or surface, rather than confined, water. We used quasielastic neutron scattering to perform a detailed investigation of the dependence of microscopic dynamics of these adsorbed water species on the hydration level and temperature. The behavior of hydration water in ultramicroporous carbon clearly demonstrates the same universal traits that characterize surface (hydration) water in other materials that are surface-hydrated. Thus, unless special treatment is intentionally applied to ultramicroporous carbon, the species filling its pores in various applications, ranging from hydrogen molecules to electrolytes, likely find themselves in contact with non-freezing water molecules characterized by rich microscopic dynamics. Graphical abstract: